Long-Term Safety Analysis of a Fibrinogen Concentrate (RiaSTAP®/Haemocomplettan® P) - Rahe-Meyer, Niels; Neumann, Gabriele; Schmidt, Dirk S; Downey, Laura A (Clinical and applied thrombosis/hemostasis, 2024)
Fibrinogen concentrate treatment is recommended for acute bleeding episodes in adult and pediatric patients with congenital and acquired fibrinogen deficiency. Previous studies have reported a low risk of thromboembolic events (TEEs) with fibrinogen concentrate use; however, the post-treatment TEE risk remains a concern. A retrospective evaluation of RiaSTAP®/Haemocomplettan® P (CSL Behring, Marburg, Germany) post-marketing data was performed (January 1986–June 2022), complemented by a literature review of published studies. Approximately 7.45 million grams of fibrinogen concentrate was administered during the review period. Adverse drug reactions (ADRs) were reported in 337 patients, and 81 (24.0%) of these patients experienced possible TEEs, including 14/81 (17.3%) who experienced fatal outcomes. Risk factors and the administration of other coagulation products existed in most cases, providing alternative explanations. The literature review identified 52 high-ranking studies with fibrinogen concentrate across various clinical areas, including 26 randomized controlled trials. Overall, a higher number of comparative studies showed lower rates of ADRs and/or TEEs in the fibrinogen group versus the comparison group(s) compared with those that reported higher rates or no differences between groups. Post-marketing data and clinical studies demonstrate a low rate of ADRs, including TEEs, with fibrinogen concentrate treatment. These findings suggest a favorable safety profile of fibrinogen concentrate, placing it among the first-line treatments effective for managing intraoperative hemostatic bleeding.